Gastrointestinal Endoscopy Performed by Gastroenterologists: Opportunistic Screening Strategy for Newly Diagnosed Head and Neck Cancers - Yang, Chih-Wei; Chu, Yueng-Hsiang; Chen, Hsin-Chien; Huang, Wei-Chen; Chen, Peng-Jen; Chang, Wei-Kuo (Frontiers in Oncology, 2022)
Aim: Approximately 66% of head and neck cancers are diagnosed at an advanced stage. This prospective study aimed to detect newly diagnosed head and neck cancers, by using regular upper gastrointestinal (UGI) endoscopy with oral-pharynx-larynx examination. Methods: Total of 2,849 patients underwent UGI endoscopy with an additional oral-pharynx-larynx examination. Patients aged < 20 years, those who were pregnant, history of head and neck cancers, undergoing emergency endoscopy, and have poor laryngopharyngeal view were excluded. The symptoms, incidence, location, pathology, and stage of malignant neoplasms were investigated. Results: Total of 2,720 patients were enrolled. Endoscopically observable 23 abnormal findings (0.85%) included 18 (0.66%) benign lesions and 5 (0.18%) newly diagnosed malignant neoplasms. Notably, 4 (80%) of 5 malignant neoplasm patients were diagnosed at an early stage (Stage 0, I, and II). Conclusions: UGI endoscopy with oral-pharynx-larynx examination can achieve opportunistic head neck cancer screening and is recommended for every patient in endoscopy units.